Modeling and defining the pervasive games and its components from a perspective of the player experience - Arango-López, Jeferson (2018)
The rapidly growth of the Pervasive Games (PG) field has allowed people to enjoy these games daily in different ways. However, developers and researchers still do not have a complete understanding of its components and features. These games have evolved in many ways depending on their field of application. That is why, for each application field the term PG has a different definition depending on its targets, devices used and research context. That is comprehensible from a technical point of view due to every research field needs to implement their own characteristics. A previous literature review was carried out [1] aiming to find definitions, methodologies to build PG, and software metrics for them. But considering that a definition was not found based on the player experience, we decided to delve into this topic. In this paper, we present a summary of definitions of PG presented by several researchers in order to check and collect their particularities. In addition, we presented a conceptual diagram of the components of PG as well, which has been the starting point to build an ontology to represent the PG meaning and its components.